Зменшувальні форми слів в українській мові: параметри лексикографічного опису - Самойлова, І. (Лексикографічний бюлетень, 2018)
The article is devoted to the description of diminutive nouns in two dictionaries:Dictionary of the Ukrainian language in 11 volumes and the Dictionary of the Ukrainian language edited by Boris Grinchenko. Thematic groups of diminutives were outlined. The semantic structure of derivatives in both dictionaries, diminutivization stages on specific examples is considered. Dictionary entries were presented where the diminutive derivatives corresponded to the original word forms. Stylistic remarks are named that can mark diminutive nouns in dictionary entries.